Contributions of extracellular-signal regulated kinase 1/2 activity to the memory trace - Santiago Ojea Ramos; Mariana Feld; María Sol Fustiñana (Frontiers in Molecular Neuroscience, 2022)
The ability to learn from experience and consequently adapt our behavior is one of the most fundamental capacities enabled by complex and plastic nervous systems. Next to cellular and systems-level changes, learning and memory formation crucially depends on molecular signaling mechanisms. In particular, the extracellular-signal regulated kinase 1/2 (ERK), historically studied in the context of tumor growth and proliferation, has been shown to affect synaptic transmission, regulation of neuronal gene expression and protein synthesis leading to structural synaptic changes. However, to what extent the effects of ERK are specifically related to memory formation and stabilization, or merely the result of general neuronal activation, remains unknown. Here, we review the signals leading to ERK activation in the nervous system, the subcellular ERK targets associated with learning-related plasticity, and how neurons with activated ERK signaling may contribute to the formation of the memory trace.